Persistence of Left Superior Vena Cava in Nonagenarian Undergoing Pacemaker Implant: Case Report - Oliveira, Lucas Hollanda; Luize, Christian Moreno; Carvalho, Ricardo Sobral de; Carvalho, Marcel Fernando Silva; Lago, Danusa Moreira; Dietrich, Cristiano de Oliveira; Cirenza, Claudio (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Introduction: The persistence of the left superior vena cava (PLSVC) is a congenital malformation of the veins that drain blood from the upper body, causing the flow to the right atrium to be processed through the coronary sinus. Case report: We describe the case of a nonagenarian woman, previously asymptomatic until she developed total atrioventricular block when she was referred for implantation of a double chamber pacemaker. Persistence of the left superior vena cava was detected during the procedure and confirmed by venography. The implantation of the electrodes was performed safely and without complications. Conclusion: Despite not usually causing symptoms, the presence of PLSVC can make invasive procedures a challenging task. Knowledge of anatomy and the use of simple techniques can facilitate interventions in this scenario.